2020
DOI: 10.1021/acsmaterialslett.0c00153
|View full text |Cite
|
Sign up to set email alerts
|

Graphoepitaxy-Directed Assembly of Organic Semiconductor Single Crystals into Trellis Structures

Abstract: In the field of organic electronics, organizing crystals into structures that promote efficient optoelectronic processes during rapid solution processing remains an outstanding challenge. Here, nanopillar grids are employed to direct the crystallization of organic semiconductor perylene during continuous solution-phase dip coating. These platelike crystals are found to orient in two distinct out-of-plane orientations with the large-area faces either parallel or perpendicular to the substrate surface. Perpendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In line with our previous work, 24 perylene crystals deposited from solution into nanopillar scaffolds exhibited orientation in the x-y plane and in the z direction for both nanopillar edge-toedge spacings, as displayed in Fig. 2C and D.…”
Section: Scaffolds With M =supporting
confidence: 91%
See 3 more Smart Citations
“…In line with our previous work, 24 perylene crystals deposited from solution into nanopillar scaffolds exhibited orientation in the x-y plane and in the z direction for both nanopillar edge-toedge spacings, as displayed in Fig. 2C and D.…”
Section: Scaffolds With M =supporting
confidence: 91%
“…Previous X-ray diffraction measurements confirmed that perylene adopts the a-phase. 24 This phase is also evident by the 921 corners of the perylene crystals. For comparison, b-perylene crystals adopt a rhombohedral shape with corner angles of 1221 and 581.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This size‐dependent dissolution and growth process is driven by chemical potential differences between small and large crystals. [ 39 ] Meanwhile, the thickness of the tubes gradually increases. As the tubes’ structure gradually becomes more regular, the van der Waals force between them becomes stronger.…”
Section: Resultsmentioning
confidence: 99%